Rhythm of Pandanaceae - Qamaruz Zaman, Faridah; Arumugam, Ramitha; Samsudin, Suhaimi; Haron, Saleha (Universiti Putra Malaysia Press, 2017)
Essential oil is commonly used for emotional and physical wellness applications (aromatherapy). To date, approximately 3,000 varieties of essential oils have been identified. The quality of essential oil depends on the season, geographic location, method and duration of distillation, year the extract plant is grown, and the climate.